Iowa RBA, August 25, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for August 25, 1997. Highlights of the update include sightings of Little Blue Herons, Red-necked Phalaropes, and a Snowy Egret. Also of note was the increase in numbers of Warblers and other migrating Passerines as well as several reports of Ospreys. Epson - sheet feed/flatbed